Women, War, and World Order: Gender Difference in Security Attitudes in Europe and the United States, 2002-2011. - Eichenberg, Richard C., 1952- (Tufts University. Tisch Library., 2016)
This paper focuses on a change in the politics of democratic societies with important implications for national security policy: the increasing political mobilization of women. This change takes several forms, including an increase in the political interest and engagement of women, a growing gender differentiation in policy preferences, and an increasing tendency of women to identify with parties of the left. Despite the importance of these changes, they have been neglected by scholars of national security. In this paper, I examine cross-national evidence on gender difference for a number of security policy issues. I draw on survey measures on a wide variety of issues, including support for international involvement, multilateral institutions, the NATO Alliance, opinions of military power and balance of power, international threats, defense spending, and the use of military force. The study covers up to 14 nations. The most important cross-national finding is that overall gender polarization on security policy issues is strongly correlated with the level of the political mobilization of women. Within nations, gender difference is most prominent on issues of military power, the cost of defense, the acceptability of war, and the use of military force. Gender difference toward international involvement and multilateral institutions are smaller. However, gender difference on each of these issues show variation by nation and over time, which suggests that particular contexts condition the degree of gender polarization. Hypotheses that cast gender difference as universal are therefore suspect. I conclude with a discussion of the implications of the findings for theories of gender difference and for the politics of Western security.